Aplasia segmentar bilateral do epididimo na espécie bubalina: relato de caso - Siqueira, Jeanne Broch; Oba, Eunice [UNESP]; Bittencourt, Rodrifo Freitas; Ferreira, João Carlos Pinheiro [UNESP]; Pinho, Rogério Oliveira; Guimarães, José Domingos (My University, 2012)
This case report involves a slaughtered cross-breed buffalo, age 27 months, carcass weight, 188 kg, without reproductive history. Blood was collected for later hormone determination. Testes and epididymes were evaluated macroscopically and microscopically. The testes were symmetrical. However, the epididymal tails were absent and the epididymal heads had cysts. Testicular parenchyma and mediastinum were swollen. Testosterone and androstenedione concentrations were 9.88 pg/mL and 3.00 ng/mL, respectively. A high degree of testicular degeneration was observed. That this condition causes esterility, coupled with the genetic origin of the disease, it is suggested that affected animals are culled.

Este estudo reporta um bubalino mestiço, com 27 meses de idade, 188 kg de peso de carcaça, sem histórico reprodutivo. Sangue foi coletado para posterior determinação hormonal. Testículos e epidídimos foram avaliados macroscopicamente e microscopicamente. Os testículos apresentaram-se simétricos, caudas dos epidídimos ausentes e cabeças com presença de cistos. Parênquima testicular e mediastino demonstraram edema. Concentrações de testosterona e androstenediona foram de, respectivamente, 9,88 pg/mL e 3,00 ng/mL. Observou-se alto grau de degeneração testicular. Considerando-se a esterilidade do animal, associada à origem genética da patologia, sugere-se que machos acometidos sejam descartados da reprodução.
A case of bilateral segmental aplasia of the epididymis in a buffalo
Keywords: Buffalo; Epididymides; Segmental aplasia; Testis; Aplasia segmentar; Búfalos; Epidídimos; Testículos